2012
DOI: 10.4174/jkss.2012.82.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Large tubular colonic duplication in an adult treated with a small midline incision

Abstract: Tubular colonic duplication presenting in adults is rare and difficult to diagnose preoperatively. Only a few cases have been reported in the literature. We report a case of a 29-year-old lady presenting with a long history of chronic constipation, abdominal mass and repeated episodes of abdominal pain. The abdominal-pelvic computed tomography scan showed segmental bowel wall thickening thought to be small bowel, and dilatation with stasis of intraluminal content. The provisional diagnosis was small bowel dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…GI duplications can cause non-specific symptoms such as abdominal mass, pain and chronic constipation, and result in complications: intestinal obstruction, subvolvulus, volvulus, torsion, intussusceptions, haemorrhage, perforation and fistulas. Symptoms might be caused by duplication colon distinction, adjacent organ compression or compression of the coeliac plexus 7 8. Duplication has been extended, displaced transverse and sigmoid colon in our case.…”
Section: Discussionmentioning
confidence: 59%
“…GI duplications can cause non-specific symptoms such as abdominal mass, pain and chronic constipation, and result in complications: intestinal obstruction, subvolvulus, volvulus, torsion, intussusceptions, haemorrhage, perforation and fistulas. Symptoms might be caused by duplication colon distinction, adjacent organ compression or compression of the coeliac plexus 7 8. Duplication has been extended, displaced transverse and sigmoid colon in our case.…”
Section: Discussionmentioning
confidence: 59%
“…Despite the initial colonoscopy, the duplication remained unnoticed due to its cystic structure and the lack of luminal relation. In literature, CT scanning findings have been reported to be confused with other conditions such as cystic pancreatic tumors, mesenteric inflammatory masses, or Meckel's diverticulum, although it may help in the diagnosis of colonic duplications [2]. Often the duplication is diagnosed during the operation nonetheless our case was diagnosed only after the pathological examination.…”
Section: Discussionmentioning
confidence: 77%
“…They are rarely found in the colon and very few cases have been described in adults [1]. Clinical features of colonic duplication include vague abdominal pain, abdominal mass, and chronic constipation all of which occur due to pressure or direct effects of the lesion [2]. Although they are benign, some fatal consequences may arise if they are not treated appropriately [3].…”
Section: Introductionmentioning
confidence: 99%
“…The tubular type includes the double-barreled type (80%) and the Y- or T-shaped type (20%) [ 8 ]. Therefore, tubular colonic duplications in adults are very rare, and in our literature review, only 17 cases have been reported [ 4 ]. Tubular and Y-shaped total colonic duplications in adults are extremely rare, and we have not found any other cases.…”
Section: Discussionmentioning
confidence: 99%
“…Among all duplications, colonic duplication is more rare and complete duplication of the colon in adults is very rare and difficult to diagnose preoperatively. Only few cases have been reported in the literature [ 2 3 4 ]. In children, several cases of duplication of pouch colon associated with duplication of the lower genitourinary tract have been reported [ 5 ].…”
Section: Introductionmentioning
confidence: 99%